KEBIJAKAN MODERASI PIDANA MATI - Mei Susanto; Ajie Ramdan (Komisi Yudisial RI, 2017)
ABSTRAKPutusan Nomor 2-3/PUU-V/2007 selain menjadi dasar konstitusionalitas pidana mati, juga memberikan jalan tengah (moderasi) terhadap perdebatan antara kelompok yang ingin mempertahankan (retensionis) dan yang ingin menghapus (abolisionis) pidana mati. Permasalahan dalam penelitian ini adalah bagaimana kebijakan moderasi pidana mati dalam putusan a quo dikaitkan dengan teori pemidanaan dan hak asasi manusia dan bagaimana kebijakan moderasi pidana mati dalam RKUHP tahun 2015 dikaitkan dengan putusan a quo. Penelitian ini merupakan penelitian doktrinal, dengan menggunakan bahan hukum primer dan sekunder, berupa peraturan perundang-undangan, literatur, dan hasil-hasil penelitian yang relevan dengan objek penelitian. Penelitian menyimpulkan, pertama, putusan a quo yang memuat kebijakan moderasi pidana mati telah sesuai dengan teori pemidanaan khususnya teori integratif dan teori hak asasi manusia di Indonesia di mana hak hidup tetap dibatasi oleh kewajiban asasi yang diatur dengan undang-undang. Kedua, model kebijakan moderasi pidana mati dalam RKUHP tahun 2015 beberapa di antaranya telah mengakomodasi amanat putusan a quo, seperti penentuan pidana mati di luar pidana pokok, penundaan pidana mati, kemungkinan pengubahan pidana mati menjadi pidana seumur hidup atau penjara paling lama 20 tahun. Selain itu masih menimbulkan persoalan berkaitan dengan lembaga yang memberikan pengubahan pidana mati, persoalan grasi, lamanya penundaan pelaksanaan pidana mati, dan jenis pidana apa saja yang dapat diancamkan pidana mati.Kata kunci: kebijakan, KUHP, moderasi, pidana mati. ABSTRACTConstitutional Court’s Decision Number 2-3/PUU-V/2007, in addition to being the basis of the constitutionality of capital punishment, also provides a moderate way of arguing between retentionist groups and those wishing to abolish the death penalty (abolitionist). The problem in this research is how the moderation policy of capital punishment in aquo decision is associated with the theory of punishment and human rights and how the moderation policy of capital punishment in the draft Criminal Code of 2015 (RKUHP) is related with the a quo decision. This study is doctrinal, using primary and secondary legal materials, in the form of legislation, literature and research results that are relevant to the object of analysis. This study concludes, firstly, the aquo decision containing the moderation policy of capital punishment has been in accordance with the theory of punishment, specificallyy the integrative theory and the theory of human rights in Indonesia, in which the right to life remains limited by the fundamental obligations set forth in the law. Secondly, some of the modes of moderation model of capital punishment in RKUHP of 2015 have accommodated the mandate of aquo decision, such as the determination of capital punishment outside the main punishment, postponement of capital punishment, the possibility of converting capital punishment to life imprisonment or imprisonment of 20 years. In addition, it still raises issues regarding the institutions that provide for conversion of capital punishment, pardon matters, length of delay in the execution of capital punishment, and any types of crime punishable by capital punishment. Keywords: policy, criminal code, moderation, capital punishment.